2006
DOI: 10.1017/s1121189x00004425
|View full text |Cite
|
Sign up to set email alerts
|

Cross-cultural studies of personality traits and their relevance to psychiatry

Abstract: Aims-This article provides a brief review of recent cross-cultural research on personality traits at both individual and culture levels, highlighting the relevance of recent findings for psychiatry.Method-In most cultures around the world, personality traits can be clearly summarized by the five broad dimensions of the Five-Factor Model (FFM), which makes it feasible to compare cultures on personality and psychopathology.Results-Maturational patterns and sex differences in personality traits generally show cul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
34
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 73 publications
4
34
0
1
Order By: Relevance
“…Scores followed a normal distribution and were standardized using combined gender American norms (Costa and McCrae 1992). The NEO-PI-R has a robust factor structure that has been replicated in Italy (Terracciano 2003) and in more than 50 cultures (McCrae et al, 2005; Terracciano and McCrae 2006). Stability coefficients for the five factors are in the range of 0.80 over intervals of 10 years (Terracciano et al, 2006).…”
Section: Methodsmentioning
confidence: 99%
“…Scores followed a normal distribution and were standardized using combined gender American norms (Costa and McCrae 1992). The NEO-PI-R has a robust factor structure that has been replicated in Italy (Terracciano 2003) and in more than 50 cultures (McCrae et al, 2005; Terracciano and McCrae 2006). Stability coefficients for the five factors are in the range of 0.80 over intervals of 10 years (Terracciano et al, 2006).…”
Section: Methodsmentioning
confidence: 99%
“…In part, this association is thought to be based on the impact of personality on health risk behaviors, such as those contributing to obesity, sexually transmitted disease, or cigarette smoking (1, 58), which are leading causes of disability and death (9, 10). In addition, personality traits are related to psychopathology (1113), coping mechanisms (14), adherence to medical treatment (15, 16), well-being (17), as well as interpersonal relations and social integration (18), which in turn are all related to health outcomes (19, 20). …”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated that the Five Factor Model of Dimensional Analysis (FFM) has a strong correlation with DSM-IV findings, has a more descriptive and accurate approach for comorbid illnesses found with BPD, and has a large level of cross-cultural reproducibility (Lynam & Widiger, 2001). Terracciano and McCrae (2006) reviewed cross-cultural research on personality traits at both individual and culture levels. They found that the average personality profiles from 51…”
Section: Reviewed Black and Hispanicmentioning
confidence: 99%